2021
DOI: 10.3389/fpsyt.2021.701032
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Psychological Health of Frontline Health Workers in Wuhan Under and After the Lockdown

Abstract: Background: The coronavirus disease-2019 (COVID-19) outbreak and a 3-month lockdown of Wuhan may have had a long-term impact on the mental health of frontline healthcare workers (HWs). However, there is still a lack of comparative studies on the mental health of front-line HWs in the initial phase of the lockdown and 1 month after the lifting of the lockdown.Methods: We recruited 1717 HWs during the initial phase of the lockdown and 2214 HWs 1 month after the lifting of the lockdown, and their baseline charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(72 reference statements)
2
4
1
1
Order By: Relevance
“…Similar results have been found in the general population of Nigeria during the COVID-19 lockdown [ 43 ]. This finding contrasted with other results showing differences in lower annual household income, family members or relatives with suspected or confirmed SARS-CoV-2 infection, comorbidity, deteriorating relationships with family members [ 34 ], age (31–40 year group), educational background, and appraisal of the threat of infection by the virus [ 44 ]. We also analyzed several key influencing factors and found that smoking, drinking alcohol, exercising, and being satisfied with welfare all substantially influenced mental status.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Similar results have been found in the general population of Nigeria during the COVID-19 lockdown [ 43 ]. This finding contrasted with other results showing differences in lower annual household income, family members or relatives with suspected or confirmed SARS-CoV-2 infection, comorbidity, deteriorating relationships with family members [ 34 ], age (31–40 year group), educational background, and appraisal of the threat of infection by the virus [ 44 ]. We also analyzed several key influencing factors and found that smoking, drinking alcohol, exercising, and being satisfied with welfare all substantially influenced mental status.…”
Section: Discussioncontrasting
confidence: 97%
“…Previous studies have suggested that medical workers are particularly vulnerable to mental health problems even during times of a relative epidemic decline [ 40 , 41 ]. Other results have suggested that stress and fatigue among front-line health workers may be associated with the risk of adverse mental health outcomes [ 14 , 26 , 34 ]. Our results are largely consistent with those of other studies, which have reported that, during major public health emergencies, medical staff face a risk of experiencing serious mental health consequences due to high-intensity fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with previous studies performed during the pandemic reporting high rates of mental health problems among HCWs [ 39 ]. However, our study’s prevalence of depression, anxiety, and stress was lower than those obtained in a Chinese study during the critical pandemic period that showed 37.8% of depression, 43.0% of anxiety, and 38.5% of stress among HCWs from different provinces [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…2021 ; Ide et al., 2021 ; Ifthikar et al., 2021 ; Ilias et al., 2021 ; Jang et al., 2021 ; Jemal et al., 2021 ; Ji et al., 2021 ; Johnson et al., 2020 ; Jo et al., 2020 ; Juan et al., 2020 ; Kiefer et al., 2021 ; Kumar et al., 2021 ; Lamiani et al., 2021 ; Lange et al., 2022 ; Lasalvia et al., 2021 ; Lasalvia et al., 2022 ; Laurent et al., 2022 ; León Rojas et al., 2022 ; Li et al., 2021 , 2020 ; Liu et al., 2021 ; Luceño-Moreno et al., 2020 ; Lum et al., 2021 ; Luo et al., 2021 ; Magalhaes et al., 2021 ; Manh Than et al., 2020 ; Marco et al., 2020; Marcomini et al., 2021 ; Martín et al., 2021 ; Meena et al., 2022 ; Mehta et al., 2022 ; Mirzaei et al., 2022 ; Moderato et al., 2021 ; Mulatu et al., 2021 ; Naheed et al., 2021 ; Nguyen et al., 2021 ; Nguyen et al., 2021 ; Ouyang et al., 2022 ; Pan et al., n.d. ; Pappa et al., 2021 ; Prasad et al., 2020 ; Qiu et al., 2021 ; Ranieri et al., 2021 ; Riello et al., 2020 ; Robles et al., 2021 ; Rosenthal et al., 2021 ; Rouse and Regan, 2021 ; Sachdeva et al., 2021 ; Sahin et al., 2022 ; Sarapultseva et al., 2021 ; Shah et al., 2021 ; Sobregrau Sangrà et al., 2022 ; Styra et al., 2021 ; Tebbeb et al., 2022 ; Topal et a...…”
Section: Resultsunclassified